Chapter Costruire offerta formativa in Higher Education: la sfida di accompagnare la ricerca - TOGNI, Fabio (Studies on Adult Learning and Education, 2022)
The design of Higher Education courses requires a systemic and integrated vision and an approach that starts with the research practice. This contribution aims to show how, in the history of Higher Education, some suggestions are hidden to activate design looks that have at heart the integral training of doctoral students, understood as practitioner-scholars. The case study of the PhD in Education and Psychology of the University of Florence aims to bring out the many challenges that national and international transformations offer to and in the Third Level of HE.